Phylogeny, ultrastructure and histopathology of Myxobolus lomi sp nov., a parasite of Prochilodus lineatus (Valenciennes, 1836) (Characiformes: Prochilodontidae) from the Peixes River, Sao Paulo State, Brazil - Azevedo, Rodney Kozlowiski; Mirandola Dias Vieira, Diego Henrique [UNESP]; Vieira, Gustavo Henrique [UNESP]; Silva, Reinaldo Jose [UNESP]; Matos, Edilson; Abdallah, Vanessa Doro (Elsevier B.V., 2014)
This paper presents the morphological, histological, molecular and ultrastructural data on Myxobolus lomi sp. nov., a parasite of the gill filaments of Prochilodus lineatus from the Peixes River (48(Omega)06'138W; 22(Omega) 49'53.1S), Sao Paulo State, Brazil. From 20 P. lineatus specimens examined, 90.0% (n = 18) were infected. The plasmodia were white and round, measuring 250 to 300 pm in diameter and the development occurred in the base of the gill filament. The spores showed symmetrical and smooth valves, with the polar filament having 8 to 11 coils. A thorough comparison with all the Myxobolus species described so far is provided. A partial sequencing of the 18S rDNA gene revealed approximately 1600-bp. The Myxobolus species parasite of P. lineatus did not match any of the Myxozoa available in GenBank. In the phylogenetic analysis, M. lomi sp. nov. is clustered with ten other species and only four of these parasites were from gills. Histological analysis of P. lineatus gills infected by M. lomi sp. nov. revealed numerous well-delimited cysts at the base of the primary lamella, between connective tissue and bone, next to the gill arteries. However no pronounced inflammatory response was found at the infection site. (c) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Phylogeny; Ultrastructure; Histopathology; Myxobolus lomi sp nov.; Prochilodus lineatus; Brazil